Focus on Family Historians How Ancestor Research Affects Self-Understanding and Well-Being - Moore, Susan M; Rosenthal, Doreen (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The articles in this Special Issue of Genealogy titled "Focus of Family Historians: How Ancestor Research Affects Self-Understanding and Well-Being" cover topics including the psychosocial motivations that impel family history research, its therapeutic and healing aspects, and the emotional outcomes of dealing with unexpected findings. Broader issues, such as the ubiquity of ancestral acknowledgement and veneration throughout history and its links with religion are also explored. Papers include scholarly interpretations of case-based material, empirical research, and interpretive literature reviews emanating from a wide range of social science disciplines.